Miscibility of isotactic polypropylene with random and block ethylene-octene copolymers studied by atomic force microscopy-infrared. (27th October 2022) - Zhong, Zhenxing; Peng, Li; Zhang, Na; Su, Juanxia; Ye, Nanbiao; Luo, Zhongfu; Han, Charles C.; Huang, Xianbo; Su, Zhaohui
Abstract: Ethylene-octene random copolymers (EOCs) and block copolymers (OBCs) have been used extensively in toughening isotactic polypropylene (iPP). In this work, the miscibility of iPP/EOC and iPP/OBC blends has been investigated quantitatively using an atomic force microscopy-infrared (AFM-IR) technique. A blend of a partially deuterated iPP and EOC at 80/20 mass ratio was found to phase separate, and in situ AFM-IR analysis revealed the presence of deuterated iPP in both phases, indicating partial miscibility between the two components. Quantitation methods for phase compositions of iPP/EOC and iPP/OBC blends using AFM-IR were established, and phase separation kinetics for a solution-mixed iPP/OBC 50/50 blend at 200 °C was investigated using AFM-IR. The phase compositions reach an equilibrium state in ∼4 h, and each component exhibits a solubility of ∼10 wt% in the other one in the molten state. Moreover, an interphase of ∼1 μm thickness and transitional composition is present in between the iPP-rich and the OBC-rich phases, indicative of good compatibility between iPP and OBC. In contrast, an iPP/EOC 50/50 blend under the same conditions contains two co-existing phases, with an EOC content of 4.9 and 93.2 wt% for the iPP-rich and EOC-rich phase, respectively, with a sharp interface between, implying poorer compatibility of EOC with iPP than for OBC. Composition analyses for iPP/EOC 80/20 and iPP/OBC 80/20 blends prepared by melt-blending support these observations. Graphical abstract: Image 1 Highlights: Miscibility of iPP/POE blends is investigated quantitatively. OBC and iPP each exhibits a solubility of ∼10 wt% in the other. An interphase exists between the two phases in iPP/OBC blends. OBC is more compatible with iPP than EOC.